2005
DOI: 10.1027/1015-5759.21.4.226
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bidirectional Influences Between Family Relationships and Adolescent Problem Behavior

Abstract: Abstract. In family research, bidirectional influences between the family and the individual are usually analyzed in discrete time. Results from discrete time analysis, however, have been shown to be highly dependent on the length of the observation interval. Continuous time analysis using stochastic differential equations has been proposed to circumvent this problem. The present study examined the bidirectional influences between family relationships and adolescent problem behavior by means of both discrete- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…This finding is consistent with Delsing et al (2005), who found that family justice was very stable over time. Other studies have also shown that family-level interaction does not change much over time (Godley et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…This finding is consistent with Delsing et al (2005), who found that family justice was very stable over time. Other studies have also shown that family-level interaction does not change much over time (Godley et al, 2005).…”
Section: Discussionsupporting
confidence: 94%
“…Cross-lagged models are frequently utilized in family research to consider bidirectional effects of family characteristics and children's behavior (Delsing, Oud, & Bruyn, 2005), including studies of families with children who have developmental disabilities (Greenberg, Seltzer et al, 2006; Orsmond, Seltzer, Krauss, & Hong, 2003). We used LISREL 8.54 to test 6 two-wave, cross-lagged models.…”
Section: Resultsmentioning
confidence: 99%
“…The bidirectional view of child socialization implies that family functioning and parents influence the child's adjustment, which in turn influences the family functioning and behaviour of parents (Bell 1968). Although most previous studies have emphasized the effects of family functioning on children, few studies have examined the effects of child and his adjustment on family in longitudinal studies (e.g., Delsing et al 2005;Shek 1998Shek , 2005. Shek (1998Shek ( , 2005 found that adolescent psychological well-being is predictive of family functioning over time.…”
Section: Discussionmentioning
confidence: 96%